Abundant and dynamically expressed miRNAs, piRNAs, and other small RNAs in the vertebrate Xenopus tropicalis - Armisen, Javier; Gilchrist, Michael J.; Wilczynska, Anna; Standart, Nancy; Miska, Eric A. (Genome Research, 2009)
Small regulatory RNAs have recently emerged as key regulators of eukaryotic gene expression. Here we used high-throughput sequencing to determine small RNA populations in the germline and soma of the African clawed frog Xenopus tropicalis. We identified a number of miRNAs that were expressed in the female germline. miRNA expression profiling revealed that miR-202-5p is an oocyte-enriched miRNA. We identified two novel miRNAs that were expressed in the soma. In addition, we sequenced large numbers of Piwi-associated RNAs (piRNAs) and other endogenous small RNAs, likely representing endogenous siRNAs (endo-siRNAs). Of these, only piRNAs were restricted to the germline, suggesting that endo-siRNAs are an abundant class of small RNAs in the vertebrate soma. In the germline, both endogenous small RNAs and piRNAs mapped to many high copy number loci. Furthermore, endogenous small RNAs mapped to the same specific subsets of repetitive elements in both the soma and the germline, suggesting that these RNAs might act to silence repetitive elements in both compartments. Data presented here suggest a conserved role for miRNAs in the vertebrate germline. Furthermore, this study provides a basis for the functional analysis of small regulatory RNAs in an important vertebrate model system.